2002
DOI: 10.1042/bj20011312
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M induced α1-antitrypsin (AAT) gene expression in Hep G2 cells is mediated by a 3′ enhancer

Abstract: alpha(1)-Antitrypsin (AAT) is the major serine proteinase inhibitor (SERPIN A1) in human plasma. Its target proteinase is neutrophil elastase and its main physiological function is protection of the lower respiratory tract from the destructive effects of neutrophil elastase during an inflammatory response. Circulating levels of AAT rise 2-3-fold during inflammation and the liver produces most of this increase. The cytokines oncostatin M (OSM) and interleukin-6 have been shown to be mainly responsible for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…By the stimulation with HGF and/or OSM, hAE cells expressed α1AT more strongly. This phenomenon is similar to that reported for the hepatocyte (Guillen et al, 1996;Morgan et al, 2002). This result led us to expect that hAE cells produce α1AT.…”
Section: Human Ae Cells Express a Part Of Hepatocyte-related Genessupporting
confidence: 76%
“…By the stimulation with HGF and/or OSM, hAE cells expressed α1AT more strongly. This phenomenon is similar to that reported for the hepatocyte (Guillen et al, 1996;Morgan et al, 2002). This result led us to expect that hAE cells produce α1AT.…”
Section: Human Ae Cells Express a Part Of Hepatocyte-related Genessupporting
confidence: 76%
“…Lipoproteins may have pathophysiologic importance in lung disease 82 ; differences in apolipoprotein B have been described in association with lung function and COPD 83,84 , and a recent study identified an association between SNPs near APOM , lung function, and emphysema 85 . Similarly, our GRAIL analysis suggested a role for oncostatin M and its receptor, which may be of interest in COPD and emphysema 86,87 . Additional studies will be needed to confirm these findings.…”
Section: Discussionsupporting
confidence: 54%
“…Specifically, in the liver AAT is mainly regulated by IL-6-like cytokines including OSM. This process is mediated by the interaction between the hepatocyte promoter of SERPINA1 and an OSM response element located at the 3′UTR of the AAT gene via the interaction of transcription factors like STAT3 [25]. We found that OSM significantly up-regulates AAT expression in MM and MZ organoids under undifferentiated and differentiated stages, whereas in ZZ organoids AAT was up-regulated only after differentiation.…”
Section: Discussionmentioning
confidence: 75%